Mapping Functional Competencies for strategic Readiness in Public Utilities and Telecommunication Governance: A Case Study of Sarawak Civil Service. - Sopian, Bujang; Lee, Jun Choi; Nadri Aetis Heromi, Basmawi; Ade Syaheda Wani, Marzuki (2025)
This study investigates a strategic competency mapping initiative within the Ministry of Utilities and Telecommunication (MUT) Sarawak, undertaken to strengthen institutional readiness in response to digital transformation and emerging governance complexities. The main objective is to identify, assess, and enhance key functional competencies that underpin the ministry’s effectiveness in delivering sustainable public services. Employing a qualitativedescriptive design, the study integrates document analysis, focus group discussions (FGDs), and expert panel validation to examine workforce competencies across four strategic domains: Digitalization and Data Governance, Utility and Infrastructure Planning, Telecommunication Innovation, and Policy and Regulatory Leadership. Findings indicate significant competency gaps in areas such as digital literacy, strategic foresight, regulatory adaptability, and stakeholder engagement highlighting the need for systematic capacity-building and continuous professional development. Through thematic analysis, the study synthesizes these findings into a context sensitive competency framework that supports targeted interventions in workforce training, leadership development, and organizational restructuring. The proposed framework aligns with both local governance priorities and international competency standards, offering a structured approach to developing adaptive and future-ready human capital. Overall, the study concludes that strategic competency mapping serves as a transformative instrument for institutional reform, enabling public organizations such as MUT Sarawak to navigate digital disruptions, strengthen policy responsiveness, and sustain operational excellence. By bridging competency assessment with strategic Human Resource Development (HRD) practices, the initiative establishes a replicable model for other public institutions seeking to achieve resilience, innovation, and sustainable governance in the era of digital transformation.